Russia’s UN grain deal boomerang: Implications for the deal and global food prices - Glauber, Joseph W.; Welsh, Caitlin; Laborde Debucquet, David (Center for Strategic and International Studies, 2022)
Russia rejoined the UN Black Sea Grain Initiative on Wednesday after pausing its participation over the weekend when its Black Sea Fleet was attacked off the Crimean city of Sevastopol. The deal, signed in July for a 120-day period, is up for renewal on November 19. What do Russia’s decisions this week bode for the future of the grain deal? And what does the grain deal mean for Ukrainian agriculture and global food security?